Evaluation of two harvesting systems for the supply of wood-chips in Norway spruce forests affected by bark beetles - Tobias Cremer; Borja Velazquez-Marti (Croatian Journal of Forest Engineering, 2007)
For sanitary reasons, spruce trees affected by bark beetles (Ips typographus L.) should be re¬moved out of the stand as soon as possible, to avoid the propagation of the beetles to healthy trees. One possibility, to utilize the accruing crown material in a reasonable way (instead of burning it) could be, to use it as wood-chips for biomass heating plants. The aim of this project was therefore to determine the productivity of two harvesting and processing systems for wood-chips as a joint-product of round wood in Norway spruce (Picea abies L.) forests affected by bark beetles. Two systems with different sorting criteria were studied: processing of sawlogs, pulpwood and wood-chips (System A) in comparison to the process¬ing of only sawlogs and wood-chips (System B). In System A, the energy wood was chipped with a chipper mounted on a forwarder that was working directly in the stand. In System B, the material to be chipped was previously concentrated along the forest road with a forwarder, and a chipper mounted on a truck was used for chipping. In System A, 0.18 t of dried chips could be harvested per m3 of round wood, and in System B 0.26 t of dried chips per m3 of round wood. The cost of chipping in the stand was 4.74 ./m3 of chips and the cost of chipping along the forest road after transporting the chipping material by a forwarder was 5.63 ./m3 of chips. Therewith, a cost-covering supply of wood-chips may be obtained out of such stands. Concerning the ratio of energy input to energy output it can be said that the systems required 1.5% and 2% of energy output that was obtained using the respective system.